A highly wear-resistant water-based elastic coating
By using cage-shaped polyols and nanolinear silica wear-resistant materials in the aqueous polyurethane elastic coating, combined with the load of zinc silver ions, the problem of difficult to take into account the wear resistance and transparency of the coating is solved, and the effect of high wear resistance and good transparency is achieved.
Patent Information
- Application Number
- CN202410672697.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-28
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-05-28
AI Technical Summary
Existing water-based polyurethane elastic coatings are difficult to balance between wear resistance and transparency, resulting in the loss of natural texture and authenticity of wooden floors.
The modified polyurethane emulsion is used to contain cage-shaped polyol structural segments and nanolinear silica wear-resistant materials. Through the space network structure of cage-shaped polyol and the linear shape of nanolinear silica, the zinc silver ions loaded on the nanolinear silica are improved to improve the wear resistance and transparency of the coating.
It achieves high wear resistance and good transparency of water-based polyurethane elastic coating, taking into account the touch and natural texture of wooden floors, making it more aesthetic and practical.
Smart Images

Figure BDA0004863128140000071 
Figure BDA0004863128140000081 
Figure BDA0004863128140000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of water-based elastic coatings, and in particular to a highly wear-resistant water-based elastic coating. Background Art
[0002] Water-based elastic coating is a type of coating that uses water as the main solvent. Compared with conventional solvent-based elastic coatings, water-based elastic coatings have relatively less impact on the environment. Water-based polyurethane elastic coating is one of the more common types of water-based elastic coatings.
[0003] Polyurethane material is a substance composed of soft monomers and hard monomers connected to each other. The synergistic effect of the soft and hard ends gives it good flexibility, thermal stability and water resistance. Therefore, it is widely used in furniture, construction, wooden floors, high-end stairs and other fields.
[0004] Among them, although the adhesion of water-based polyurethane elastic coating can make the wooden floor have a better touch, since the wooden floor needs to withstand friction for a long time, higher requirements are placed on the wear resistance of the water-based polyurethane elastic coating. In order to improve the wear resistance of the water-based polyurethane elastic coating, wear-resistant materials are usually added to the high wear-resistant water-based elastic coating, but the addition of conventional wear-resistant materials will affect the transparency of the water-based polyurethane elastic coating, thereby covering up the natural texture of the wooden floor, resulting in a lack of realism in the wooden floor.
[0005] Therefore, there is an urgent need for a waterborne polyurethane elastic coating having both excellent wear resistance and transparency. Summary of the invention
[0006] In order to overcome the defect that conventional water-based polyurethane elastic coatings are difficult to have both wear resistance and transparency, the present application provides a highly wear-resistant water-based elastic coating.
[0007] The present application provides a highly wear-resistant water-based elastic coating, which adopts the following technical solution:
[0008] A highly wear-resistant water-based elastic coating comprises the following raw materials in parts by weight: 40-60 parts of modified polyurethane emulsion, 0.1-0.3 parts of wetting agent, 0.4-0.8 parts of defoaming agent, 0.3-0.7 parts of thickener, 0.4-0.8 parts of leveling agent, 1.5-3.0 parts of film-forming aid and 10-16 parts of water; the modified polyurethane emulsion contains cage-like polyol structural chain segments and nano-linear silica wear-resistant materials.
[0009] The cage-like polyol structural segment is a structural segment that simulates the cage-type oligomeric silsesquioxane (POSS) structure. It increases the crosslinking density of the polyurethane coating through the polyhydroxy structure, forms a spatial network structure, and makes the coating "hard" and stable. At the same time, the cage-like polyol has a structure similar to that of a football. When it is squeezed by external force, it has a certain shrinkable rebound performance, thus reflecting the "soft" characteristic, and then buffers the external force, reduces the external friction damage, and shows better wear resistance.
[0010] Adding appropriate powder is a common method to enhance the wear resistance of coatings. However, conventional wear-resistant powders such as silica are usually spherical particles, which have a certain extinction effect, thus affecting the transparency of the coating. Compared with spherical silica particles, linear silica coatings will have higher optical transmittance and thus better transparency.
[0011] Furthermore, when the cage-like polyol structural segments and the nano-linear silica wear-resistant material are used in combination, the prepared water-based elastic coating will have both excellent wear resistance and transparency.
[0012] Optionally, the preparation method of the nano linear silica wear-resistant material is: take 14-18g of polyvinyl pyrrolidone, then add 150-170mL of n-pentanol and mix evenly, then seal and shake for 1-3h; after fully dissolved, add 10-20mL of ethanol and 4-6mL of deionized water, mix evenly, then drip 1-2mL of sodium citrate dihydrate aqueous solution, then drip 2-4mL of ammonia water while shaking, let stand for 4-6min, then drip 1-2mL of ethyl orthosilicate, mix evenly, and place at 80-90°C for reaction for 2-4h;
[0013] Then, the mixture was filtered through a polytetrafluoroethylene membrane with a pore size of 0.45 μm, washed three times with ethanol and water respectively, and finally dried to obtain a nano-linear silica wear-resistant material.
[0014] Optionally, the nano linear silica wear-resistant material is loaded with silver ions and zinc ions.
[0015] Optionally, the method for preparing the nano linear silicon dioxide wear-resistant material comprises the following steps:
[0016] Preparation of emulsion A: 18-22 mL of surfactant was taken, followed by addition of 70-80 mL of cyclohexane, 15-20 mL of n-hexanol and 1-2 mL of deionized water, followed by mixing and stirring for 10-20 min; then 6-8 mL of 0.25 mol / L zinc nitrate solution and 80-100 μL of 0.25 mol / L silver nitrate solution were added, followed by mixing and stirring for 20-40 min to obtain emulsion A;
[0017] Preparation of emulsion B: 18-22 mL of surfactant was taken, followed by addition of 70-80 mL of cyclohexane, 15-20 mL of n-hexanol and 1-2 mL of deionized water, followed by mixing and stirring for 10-20 min; then 8-14 mL of 1 mol / L sodium hydroxide solution was added, followed by mixing and stirring for 20-40 min to obtain emulsion B;
[0018] Zinc-silver emulsion: Mix emulsion A and emulsion B for 10-14 hours to obtain zinc-silver emulsion;
[0019] Preparation of nano-linear silica wear-resistant material: Take 14-18g of polyvinyl pyrrolidone, then add 150-170mL of n-pentanol and mix evenly, then seal and shake for 1-3h; after fully dissolved, add 10-20mL of ethanol and 4-6mL of deionized water, mix evenly, then drip 1-2mL of sodium citrate dihydrate aqueous solution, and then drip 2-4mL of ammonia water while shaking, let stand for 4-6min, then drip 1-2mL of ethyl orthosilicate, mix evenly, and place at 80-90℃ to react for 1-3h; then add the above-mentioned zinc-silver emulsion and place at 80-90℃ to react for 3-5h, then hydrolyze at 140℃ for 5h, and finally wash and dry to obtain the nano-linear silica wear-resistant material.
[0020] Although nanolinear silica has excellent optical transmittance, its linear shape restricts its wear resistance. When zinc-silver ions are loaded on the nanolinear silica, the nanolinear silica and the zinc-silver ions will form a dot-line structure in which linear particles coexist, thereby effectively enhancing the wear resistance of the nanolinear silica.
[0021] In addition, during the actual use of wooden floors, the antibacterial properties of the wooden floors themselves also need to be noted. When zinc and silver ions are loaded on nano-linear silica, the zinc and silver ions can also interact with the negative ions of bacterial cells, causing the enzymes and other protein mechanisms in the bacterial cells to become abnormal, thereby destroying their biofilms and metabolic basis, thus achieving the effect of antibacterial sterilization.
[0022] Optionally, the amount of the 0.25 mol / L zinc nitrate solution added is 7 ml, and the amount of the 0.25 mol / L silver nitrate solution added is 90 μL.
[0023] When the zinc nitrate solution and the silver nitrate solution are added in the above amounts, the prepared elastic coating will have better wear resistance and antibacterial properties, and the light transmittance will not be significantly reduced.
[0024] Optionally, the modified polyurethane emulsion includes the following raw materials in parts by mass: 10-20 parts of caged polyol, 10-20 parts of curing agent, 10-14 parts of nano linear silica wear-resistant material, 8-16 parts of hydroxyethyl methacrylate, 5-10 parts of 3-butylenetriethoxysilane, 10-20 parts of toluene-3,5-diisocyanate, 8-12 parts of N,N-dimethylformamide, 10-14 parts of azobisisobutyronitrile, 8-12 parts of ethyl acetate, 4-6 parts of triethylamine, 10-14 parts of dodecafluoroheptyl methacrylate and 4-6 parts of dibutyltin dilaurate.
[0025] Optionally, the preparation method of the cage polyol is: 4-5g of polycaprolactone diol, 2-4g of polycaprolactone tetraol and 8-12g of ethyl acetate are mixed and dehydrated, then 2-3g of dicyclohexylmethane diisocyanate is added, and then reacted at 50-70°C for 2-3h, then the temperature is reduced by 10-15°C and 75-85g of butyl acetate is added for stirring and dispersion, and finally the solvent is evaporated until the solid content reaches 50%, to obtain a cage polyol;
[0026] The preparation method of the curing agent is as follows: 2-3g of dicyclohexylmethane diisocyanate and 2-3g of butyl acetate are mixed, and then 2-3g of polycaprolactone tetraol and 2-3g of butyl acetate are added dropwise at a temperature of 50-70°C, and after the addition is completed, the temperature is kept at 70-90°C for 4h, and finally cooled to room temperature to obtain the curing agent.
[0027] Optionally, the preparation method of the modified polyurethane emulsion comprises the following steps:
[0028] S1, adding nano linear silica wear-resistant material to 3-butylene triethoxysilane and mixing to obtain modified nano linear silica wear-resistant material;
[0029] S2, hydroxyethyl methacrylate, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, and ethyl acetate are mixed, and then the modified nano-linear silica wear-resistant material is added while stirring at a temperature of 90-95° C., and then reacted for 5-7 hours, cooled to 40-50° C., and triethylamine is added for neutralization to obtain an intermediate;
[0030] S3. The intermediate, toluene-3,5-diisocyanate, N,N-dimethylformamide and caged polyol are mixed, and then dibutyltin dilaurate is added while stirring at a temperature of 60-80°C, followed by reaction for 6-8h, and finally a curing agent is added and mixed to obtain a modified polyurethane emulsion.
[0031] During the use of wooden floors, food and domestic water often fall on them, so there are certain requirements for the waterproof and oil-proof properties of wooden floors. The perfluorinated chain segment of dodecafluoroheptyl methacrylate has excellent hydrophobic and oleophobic effects, which in turn gives the elastic coating excellent waterproof and oil-proof properties.
[0032] Hydroxyethyl methacrylate, dodecafluoroheptyl methacrylate and 3-butenetriethoxysilane all contain double bonds, so under the action of the initiator, the three can be connected in sequence. Among them, 3-butenetriethoxysilane can be connected with the nano-linear silica wear-resistant material through coupling.
[0033] In addition, both hydroxyethyl methacrylate and caged polyol contain hydroxyl groups. Under the action of toluene-3,5-diisocyanate and a catalyst, toluene-3,5-diisocyanate can connect the caged polyol with the intermediate, thereby forming a stable multi-cross-linked network structure, further improving the wear resistance, waterproof and oil-proof properties, light transmittance and antibacterial properties of the elastic coating.
[0034] Optionally, the preparation method of the highly wear-resistant water-based elastic coating is: first add a wetting agent, a defoaming agent, a thickener, a leveling agent and a film-forming aid to water, then mix and stir for 10-15 minutes, and then add a modified polyurethane emulsion and mix and stir again for 10-15 minutes to finally obtain a highly wear-resistant water-based elastic coating.
[0035] In summary, the present application includes at least one of the following beneficial technical effects:
[0036] 1. The cage-like polyol structural chain segment has a structure similar to that of a football. When it is squeezed by external force, it has a certain shrinkable rebound performance, thus reflecting the characteristics of "softness", thereby buffering the external force, reducing external friction damage, and showing better wear resistance.
[0037] 2. Adding appropriate powder is a common method to enhance the wear resistance of coatings. Compared with spherical granular silica, linear silica coatings will have higher optical transmittance and better transparency. When cage-like polyol structural segments and nano-linear silica wear-resistant materials are used in combination, the prepared water-based elastic coating will have both excellent wear resistance and transparency.
[0038] 3. When zinc and silver ions are loaded on nano-linear silica, the nano-linear silica and the zinc and silver ions will form a point-line structure in which linear particles coexist, thereby effectively enhancing the wear resistance of the nano-linear silica while also having an antibacterial and sterilization effect. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to the embodiments.
[0040] raw material
[0041] Wetting agent BASF 4063; defoamer BASF 2722; thickener ZY-5028; leveling agent STA-3333A; film-forming aid Eastman 0E300; surfactant Triton X-100; polyvinyl pyrrolidone CAS: 9003-39-8; n-pentanol CAS: 71-41-0; ethanol CAS: 64-17-5; sodium citrate dihydrate CAS: 6132-04-3; ammonia CAS: 9336-21-6; tetraethyl orthosilicate CAS: 78-10-4; cyclohexane CAS: 110-82-7; n-hexanol CAS: 111-27-3; zinc nitrate CAS: 13778-30-8; silver nitrate CAS: 7761-88-8; sodium hydroxide CAS: 1310-73-2; methacrylate hydroxy Ethyl ester CAS: 868-77-9; 3-Butenetriethoxysilane CAS: 57813-67-9; Toluene-3,5-diisocyanate CAS: 26471-62-5; N,N-dimethylformamide CAS: 68-12-2; Azobisisobutyronitrile CAS: 78-67-1; Ethyl acetate CAS: 141-78-6; Triethylamine CAS: 121-44-8; Dodecafluoroheptyl methacrylate CAS: 45285-78-7; Dibutyltin dilaurate CAS: 77-58-7; Polycaprolactone diol CAPA2054; Polycaprolactone tetraol CAPA4101; Dicyclohexylmethane diisocyanate CAS: 5124-30-1; Butyl acetate CAS: 123-86-4; Polyurethane emulsion Jinan YBL.
[0042] Example
[0043] Example 1
[0044] A highly wear-resistant water-based elastic coating is composed of the following raw materials in mass: 50 g of modified polyurethane emulsion, 0.2 g of wetting agent, 0.6 g of defoaming agent, 0.5 g of thickener, 0.6 g of leveling agent, 2.0 g of film-forming aid and 13 g of water.
[0045] The preparation method of the highly wear-resistant water-based elastic coating is as follows: first, a wetting agent, a defoaming agent, a thickener, a leveling agent and a film-forming aid are added to water, followed by mixing and stirring for 15 minutes, and then a modified polyurethane emulsion is added and mixed and stirred again for 15 minutes, and finally a highly wear-resistant water-based elastic coating is obtained.
[0046] The modified polyurethane emulsion includes the following raw materials: 15g of caged polyol, 15g of curing agent and 12g of nano-linear silica wear-resistant material.
[0047] The preparation method of the modified polyurethane emulsion is as follows: mixing caged polyol, a curing agent and a nano-linear silica wear-resistant material, and standing the mixture for 30 minutes to obtain the modified polyurethane emulsion.
[0048] The preparation method of the cage polyol is as follows: 4.5g of polycaprolactone diol, 3g of polycaprolactone tetraol and 10g of ethyl acetate are mixed and dehydrated, then 2.5g of dicyclohexylmethane diisocyanate is added, and then the mixture is reacted at 60°C for 3h, then the temperature is lowered by 12°C and 80g of butyl acetate is added for stirring and dispersion, and finally the solvent is evaporated until the solid content reaches 50% to obtain the cage polyol.
[0049] The preparation method of the curing agent is as follows: 2.5g of dicyclohexylmethane diisocyanate and 2.4g of butyl acetate are mixed, and then 2.3g of polycaprolactone tetraol and 2.6g of butyl acetate are added dropwise at a temperature of 60°C. After the addition is completed, the mixture is kept at 80°C for 4h, and finally cooled to room temperature to obtain the curing agent.
[0050] The preparation method of nano-linear silica wear-resistant material is as follows: take 16g of polyvinyl pyrrolidone, then add 160mL of n-pentanol and mix evenly, then seal and shake for 2h; after fully dissolved, add 15mL of ethanol and 5mL of deionized water, mix evenly, then drip 1.5mL of sodium citrate dihydrate aqueous solution, then drip 3mL of ammonia water while shaking, let stand for 5min, then drip 1.5mL of ethyl orthosilicate, mix evenly, and then place at 85°C for reaction for 3h;
[0051] Then, the mixture was filtered through a polytetrafluoroethylene membrane with a pore size of 0.45 μm, washed three times with ethanol and water respectively, and finally dried to obtain a nano-linear silica wear-resistant material.
[0052] Example 2-3
[0053] The difference from Example 1 is that the addition amount of each component of the highly wear-resistant water-based elastic coating is different, as shown in Table 1.
[0054] Table 1 Addition amount of each component of high wear-resistant water-based elastic coating in Examples 1-3 / g
[0055]
[0056]
[0057] Example 4
[0058] The difference from Example 1 is that the nano linear silica wear-resistant material is loaded with silver ions and zinc ions;
[0059] The preparation method of nano linear silicon dioxide wear-resistant material comprises the following steps:
[0060] Preparation of emulsion A: 20 mL of surfactant was taken, followed by addition of 75 mL of cyclohexane, 18 mL of n-hexanol and 1.5 mL of deionized water, followed by mixing and stirring for 15 min; then 7 mL of 0.25 mol / L zinc nitrate aqueous solution and 90 μL of 0.25 mol / L silver nitrate aqueous solution were added, followed by mixing and stirring for 30 min to obtain emulsion A;
[0061] Preparation of emulsion B: 20 mL of surfactant was taken, followed by addition of 75 mL of cyclohexane, 18 mL of n-hexanol and 1.5 mL of deionized water, followed by mixing and stirring for 15 min; then 12 mL of 1 mol / L sodium hydroxide solution was added, followed by mixing and stirring for 30 min to obtain emulsion B;
[0062] Zinc-silver emulsion: Mix emulsion A and emulsion B for 12 hours to obtain zinc-silver emulsion;
[0063] Preparation of nano-linear silica wear-resistant material: Take 16g of polyvinyl pyrrolidone, then add 160mL of n-pentanol and mix evenly, then seal and shake for 2h; after fully dissolved, add 15mL of ethanol and 5mL of deionized water, mix evenly and drop 1.5mL of sodium citrate dihydrate aqueous solution, then shake and drop 3mL of ammonia water, let stand for 5min and drop 1.5mL of tetraethyl orthosilicate, mix evenly and place at 85℃ to react for 2h; then add the above-mentioned zinc-silver emulsion and place at 85℃ to react for 4h, then hydrolyze at 140℃ for 5h, finally wash and dry to obtain nano-linear silica wear-resistant material.
[0064] Embodiment 5-6
[0065] The difference from Example 4 is that the added amounts of the zinc nitrate aqueous solution and the silver nitrate aqueous solution are different, as shown in Table 2.
[0066] Table 2 Addition amount of zinc nitrate aqueous solution and silver nitrate aqueous solution in Examples 4-6
[0067] Example 4 Example 5 Example 6 Zinc nitrate aqueous solution / mL 7 8 6 Silver nitrate aqueous solution / μL 90 80 100
[0068] Example 7
[0069] The difference from Example 4 is that 8 g of 3-butylenetriethoxysilane is also added to the modified polyurethane emulsion.
[0070] Example 8
[0071] The difference from Example 7 is that 12 g of dodecafluoroheptyl methacrylate is further added to the modified polyurethane emulsion.
[0072] Example 9
[0073] The difference from Example 8 is that the modified polyurethane emulsion includes the following raw materials: 15g of caged polyol, 15g of curing agent, 12g of nano-linear silica wear-resistant material, 12g of hydroxyethyl methacrylate, 8g of 3-butylenetriethoxysilane, 15g of toluene-3,5-diisocyanate, 10g of N,N-dimethylformamide, 12g of azobisisobutyronitrile, 10g of ethyl acetate, 5g of triethylamine, 12g of dodecafluoroheptyl methacrylate and 5g of dibutyltin dilaurate;
[0074] The preparation method of modified polyurethane emulsion comprises the following steps:
[0075] S1, adding nano linear silica wear-resistant material to 3-butylene triethoxysilane and mixing to obtain modified nano linear silica wear-resistant material;
[0076] S2, hydroxyethyl methacrylate, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, and ethyl acetate are mixed, and then the modified nano-linear silica wear-resistant material is added while stirring at a temperature of 95° C., and then reacted for 6 hours, cooled to 45° C., and triethylamine is added for neutralization to obtain an intermediate;
[0077] S3. The intermediate, toluene-3,5-diisocyanate, N,N-dimethylformamide and caged polyol are mixed, and then dibutyltin dilaurate is added while stirring at a temperature of 70° C., followed by reaction for 7 hours, and finally a curing agent is added and mixed to obtain a modified polyurethane emulsion.
[0078] Embodiment 10-11
[0079] The difference from Example 9 is that the added amount of each component raw material of the modified polyurethane emulsion is different, as shown in Table 3.
[0080] Table 3 Addition amount of each component of modified polyurethane emulsion in Examples 9-11 / g
[0081] Example 9 Example 10 Embodiment 11 Caged polyols 15 10 20 Curing agent 15 20 10 Nano-Linear Silica Wear-Resistant Material 12 14 10 Hydroxyethyl Methacrylate 12 8 16 3-Butyltriethoxysilane 8 5 10 Toluene-3,5-diisocyanate 15 20 10 N,N-Dimethylformamide 10 8 12 Azobisisobutyronitrile 12 10 14 Ethyl acetate 10 8 12 Triethylamine 5 4 6 Dodecafluoroheptyl methacrylate 12 14 10 Dibutyltin dilaurate 5 6 4
[0082] Comparative Example
[0083] Comparative Example 1
[0084] The difference from Example 1 is that the modified polyurethane emulsion is replaced by the polyurethane emulsion YBL with the same addition amount.
[0085] Comparative Example 2
[0086] The difference from Example 1 is that no nano linear silica wear-resistant material is added to the modified polyurethane emulsion.
[0087] Comparative Example 3
[0088] The difference from Example 1 is that the nano-linear silica wear-resistant material is replaced by nano-silicon dioxide A380.
[0089] Performance testing
[0090] Detection Methods
[0091] Three samples were taken from Examples 1-11 and Comparative Examples 1-3, respectively, and then coated on the surface of organic glass with a coating thickness of 40 μm. After surface drying, the samples were dried in a constant temperature drying oven at 80° C. for 5 hours to obtain samples.
[0092] 1. Transparent performance test
[0093] The samples of Examples 1-11 and Comparative Examples 1-3 were tested for haze using a haze meter SGW-820 to obtain initial haze and take an average value. The test data are shown in Table 4.
[0094] 2. Wear resistance test
[0095] The samples of Examples 1-11 and Comparative Examples 1-3 were subjected to 200 stroke wear using an abrasion tester (Taber5900), and then the samples were subjected to a haze test again to obtain a test haze, and then the wear resistance value was calculated, where the wear resistance value = test haze - initial haze. The test data are shown in Table 4.
[0096] 3. Waterproof and oilproof performance test
[0097] First, the samples of Example 4 and Examples 8-11 that were not subjected to the wear resistance test were weighed and recorded as M1. The samples were then placed vertically, and then 100 g of an oil-water mixture was sprayed onto the coating surface. The oil-water mixture was obtained by mixing soybean oil and water in a mass ratio of 1:1. The samples were then allowed to stand for 5 minutes, and the mass of the samples was measured again, recorded as M2. The adhesion value was then calculated, and the adhesion value = M2-M1. The test data is shown in Table 5.
[0098] Table 4 Transparent wear resistance performance of Examples 1-11 and Comparative Examples 1-2
[0099]
[0100]
[0101] Table 5 Waterproof and oilproof performance of Example 4 and Examples 8-11
[0102] Adhesion value / g Adhesion value / g Example 4 3.6 Example 10 0.6 Example 8 1.1 Embodiment 11 0.8 Example 9 0.5
[0103] Referring to Comparative Examples 1-3 and Example 1 and in combination with Table 4, it can be seen that the initial haze of Comparative Example 1 is very similar to that of Example 1, but the wear resistance value of Example 1 is significantly lower than that of Comparative Example 1, which shows that the transparency of the modified polyurethane emulsion can completely replace the conventional polyurethane emulsion, and the wear resistance is also greatly improved.
[0104] The initial haze of Comparative Example 1 and Comparative Example 2 is also very similar, but the wear resistance value of Comparative Example 2 is also significantly lower than that of Comparative Example 1, but slightly inferior to that of Example 1. This shows that both the cage-like polyol structural segment and the nano-linear silica wear-resistant material have the effect of improving the wear resistance of the coating. The reason is that the cage-like polyol structural segment is a structural segment that simulates the structure of cage-type oligomeric silsesquioxane (POSS), which increases the cross-linking density of the polyurethane coating through a polyhydroxy structure to form a spatial network structure, which makes the coating have a "hard" characteristic and a stable shape.
[0105] At the same time, the caged polyol has a football-like structure. When it is squeezed by external force, it has a certain shrinkage and rebound performance, thus showing the characteristics of "softness", and then buffering the external force, reducing the external friction damage, and showing better wear resistance. The nano-linear silica wear-resistant material is a hard material that directly enhances the wear resistance of the coating.
[0106] The wear resistance value of Comparative Example 3 is significantly lower than that of Comparative Examples 1-2, and even lower than that of Example 1, but the haze of Comparative Example 3 is much higher than that of Comparative Examples 1-2 and Example 1. The reason for this is that nano-silicon dioxide is a spherical particle, and the spherical particle has a certain extinction effect, thereby affecting the transparency of the coating. Compared with spherical particle silica, the coating using linear silica will have a higher optical transmittance, and thus show better transparency, but the improvement effect of wear resistance will also be insufficient. Therefore, when the cage-like polyol structure segment and the nano-linear silica wear-resistant material are used in combination, the prepared water-based elastic coating will have both excellent wear resistance and transparency.
[0107] Referring to Examples 1-3 and in combination with Table 4, it can be seen that, relative to Example 1, the initial haze of Examples 2-3 is slightly improved, and the wear resistance value is also significantly improved. This shows that when the components of the high wear-resistant water-based elastic coating adopt the proportions of Example 1, the prepared high wear-resistant water-based elastic coating will have both better wear resistance and transparency.
[0108] Referring to Example 1 and Examples 4-6 and in combination with Table 4, it can be seen that, relative to Example 1, the initial haze of Example 4 is slightly improved, but the wear resistance value of Example 4 is significantly reduced, which indicates that the loading of silver ions and zinc ions can effectively improve the wear resistance of the coating.
[0109] The reason is that when zinc and silver ions are loaded on nano-linear silica, the nano-linear silica and the zinc and silver ions will form a dot-line structure in which linear particles coexist, thereby effectively enhancing the wear resistance of the nano-linear silica.
[0110] Compared with Example 4, the wear resistance values of Examples 5-6 are slightly improved, which shows that when the zinc nitrate aqueous solution and the silver nitrate aqueous solution are added in the amounts of Example 4, the prepared high wear-resistant elastic coating will have better wear resistance.
[0111] With reference to Example 4 and Examples 7-8 and in combination with Table 4-5, it can be seen that the wear resistance value of Example 7 is further reduced compared with that of Example 4. The reason for this is that 3-butenetriethoxysilane can couple nano-linear silica.
[0112] The initial haze and abrasion resistance values of Examples 7-8 were basically unchanged, but the adhesion value of Example 8 was significantly reduced compared with Example 4, which shows that the addition of dodecafluoroheptyl methacrylate can improve the waterproof and oil-proof properties of the highly abrasion-resistant elastic coating.
[0113] Referring to Examples 8-11 and in combination with Tables 4-5, it can be seen that, relative to Example 8, the wear resistance of Example 9 is further reduced, and at the same time, the adhesion value is further reduced. The reason is that hydroxyethyl methacrylate, dodecafluoroheptyl methacrylate and 3-butenetriethoxysilane all contain double bonds, so under the action of the initiator, the three can be connected in sequence. Among them, 3-butenetriethoxysilane can be connected to the nano-linear silica wear-resistant material through coupling.
[0114] In addition, both hydroxyethyl methacrylate and caged polyol contain hydroxyl groups. Under the action of toluene-3,5-diisocyanate and a catalyst, toluene-3,5-diisocyanate can connect the caged polyol with the intermediate, thereby forming a stable multi-cross-linked network structure, further improving the wear resistance, waterproof and oil-proof properties, light transmittance and antibacterial properties of the elastic coating.
[0115] Compared with Example 9, the initial haze or wear resistance value or adhesion value of Examples 10-11 increases to a certain extent, which shows that when the components of the modified polyurethane emulsion adopt the proportions of Example 9, the prepared high wear-resistant elastic coating will have better wear resistance, transparency and waterproof and oil-proof properties.
[0116] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A highly wear-resistant water-based elastic coating, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of modified polyurethane emulsion, 0.1-0.3 parts of wetting agent, 0.4-0.8 parts of defoaming agent, 0.3-0.7 parts of thickener, 0.4-0.8 parts of leveling agent, 1.5-3.0 parts of film-forming aid and 10-16 parts of water; the modified polyurethane emulsion contains cage-like polyol structural chain segments and nano-linear silica wear-resistant material; The modified polyurethane emulsion comprises the following raw materials in parts by mass: 10-20 parts of caged polyol, 10-20 parts of curing agent, 10-14 parts of nano linear silica wear-resistant material, 8-16 parts of hydroxyethyl methacrylate, 5-10 parts of 3-butylene triethoxysilane, 10-20 parts of toluene-3,5-diisocyanate, 8-12 parts of N,N-dimethylformamide, 10-14 parts of azobisisobutyronitrile, 8-12 parts of ethyl acetate, 4-6 parts of triethylamine, 10-14 parts of dodecafluoroheptyl methacrylate and 4-6 parts of dibutyltin dilaurate; The preparation method of the modified polyurethane emulsion comprises the following steps: S1, adding nano linear silica wear-resistant material to 3-butylene triethoxysilane and mixing to obtain modified nano linear silica wear-resistant material; S2, hydroxyethyl methacrylate, dodecafluoroheptyl methacrylate, azobisisobutyronitrile, and ethyl acetate are mixed, and then the modified nano-linear silica wear-resistant material is added while stirring at a temperature of 90-95° C., and then reacted for 5-7 hours, cooled to 40-50° C., and triethylamine is added for neutralization to obtain an intermediate; S3. The intermediate, toluene-3,5-diisocyanate, N,N-dimethylformamide and caged polyol are mixed, and then dibutyltin dilaurate is added while stirring at a temperature of 60-80°C, followed by reaction for 6-8h, and finally a curing agent is added and mixed to obtain a modified polyurethane emulsion.
2. The highly wear-resistant water-based elastic coating according to claim 1, characterized in that: The preparation method of the nano linear silica wear-resistant material is as follows: 14-18g of polyvinyl pyrrolidone is taken, and then 150-170mL of n-pentanol is added and mixed evenly, and then the mixture is sealed and shaken for 1-3h; after being fully dissolved, 10-20mL of ethanol and 4-6mL of deionized water are added, and after mixing evenly, 1-2mL of sodium citrate dihydrate aqueous solution is dripped in, and then 2-4mL of ammonia water is dripped in while shaking, and after standing for 4-6min, 1-2mL of ethyl orthosilicate is dripped in, and after mixing evenly, the mixture is placed at a temperature of 80-90°C for reaction for 2-4h; Then, the mixture was filtered through a polytetrafluoroethylene membrane with a pore size of 0.45 μm, washed three times with ethanol and water respectively, and finally dried to obtain a nano-linear silica wear-resistant material.
3. The highly wear-resistant water-based elastic coating according to claim 1, characterized in that: The nano linear silicon dioxide wear-resistant material is loaded with silver ions and zinc ions.
4. The highly wear-resistant water-based elastic coating according to claim 3, characterized in that: The preparation method of the nano linear silicon dioxide wear-resistant material comprises the following steps: Preparation of emulsion A: 18-22 mL of surfactant was taken, followed by addition of 70-80 mL of cyclohexane, 15-20 mL of n-hexanol and 1-2 mL of deionized water, followed by mixing and stirring for 10-20 min; then 6-8 mL of 0.25 mol / L zinc nitrate solution and 80-100 μL of 0.25 mol / L silver nitrate solution were added, followed by mixing and stirring for 20-40 min to obtain emulsion A; Preparation of emulsion B: 18-22 mL of surfactant was taken, followed by addition of 70-80 mL of cyclohexane, 15-20 mL of n-hexanol and 1-2 mL of deionized water, followed by mixing and stirring for 10-20 min; then 8-14 mL of 1 mol / L sodium hydroxide solution was added, followed by mixing and stirring for 20-40 min to obtain emulsion B; Zinc-silver emulsion: Mix emulsion A and emulsion B for 10-14 hours to obtain zinc-silver emulsion; Preparation of nano-linear silica wear-resistant material: Take 14-18g of polyvinyl pyrrolidone, then add 150-170mL of n-pentanol and mix evenly, then seal and shake for 1-3h; after fully dissolved, add 10-20mL of ethanol and 4-6mL of deionized water, mix evenly, then drip 1-2mL of sodium citrate dihydrate aqueous solution, and then drip 2-4mL of ammonia water while shaking, let it stand for 4-6min, then drip 1-2mL of ethyl orthosilicate, mix evenly, and place it at 80-90℃ to react for 1-3h; then add the above-mentioned zinc-silver emulsion and place it at 80-90℃ to react for 3-5h, then hydrolyze at 140℃ for 5h, and finally wash and dry to obtain the nano-linear silica wear-resistant material.
5. The highly wear-resistant water-based elastic coating according to claim 4, characterized in that: The amount of the 0.25 mol / L zinc nitrate solution added was 7 ml, and the amount of the 0.25 mol / L silver nitrate solution added was 90 μL.
6. The highly wear-resistant water-based elastic coating according to claim 1, characterized in that: The preparation method of the cage polyol is as follows: 4-5g of polycaprolactone diol, 2-4g of polycaprolactone tetraol and 8-12g of ethyl acetate are mixed and dehydrated, then 2-3g of dicyclohexylmethane diisocyanate is added, and then the mixture is reacted at 50-70°C for 2-3h, then the temperature is lowered by 10-15°C and 75-85g of butyl acetate is added for stirring and dispersion, and finally the solvent is evaporated until the solid content reaches 50%, thereby obtaining the cage polyol; The preparation method of the curing agent is as follows: 2-3g of dicyclohexylmethane diisocyanate and 2-3g of butyl acetate are mixed, and then 2-3g of polycaprolactone tetraol and 2-3g of butyl acetate are added dropwise at a temperature of 50-70°C, and after the addition is completed, the temperature is kept at 70-90°C for 4h, and finally cooled to room temperature to obtain the curing agent.
7. The highly wear-resistant water-based elastic coating according to claim 1, characterized in that: The preparation method of the highly wear-resistant water-based elastic coating is as follows: firstly, a wetting agent, a defoaming agent, a thickener, a leveling agent and a film-forming aid are added to water, followed by mixing and stirring for 10-15 minutes, and then a modified polyurethane emulsion is added and mixed and stirred again for 10-15 minutes, and finally a highly wear-resistant water-based elastic coating is obtained.
Citation Information
Patent Citations
Method for preparing silicon dioxide cladding silver-doped zinc oxide nano crystal
CN101850980A
Waterborne antibacterial wood paint as well as preparation method and application thereof
CN108587428A
Conductive paste and preparation method thereof, conductive layer and preparation method thereof, and heating film
CN117423489A
High-wear-resistance water-based elastic coating
CN117820952A